2022
DOI: 10.3390/ma15144832
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Green Synthesis of (Fe3O4) and (NiFe2O4) Nanoparticles Using Star Anise (Illicium verum) Extract and Their Biomedical Activity against Some Cancer Cells

Abstract: Magnetite Fe3O4 and spinel (2:1) and (4:1) NiFe2O4 magnetic nanoparticles (MNPs) were prepared by simple and affordable co-precipitation methods using an extract of star anise (Illicium verum) as a green reducing agent. The morphology and chemical composition of these MNPs were confirmed by field-emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, UV–visible spectroscopy, and X-ray diffraction (XRD). The synthesized magnetite Fe3O4 and spinel (2:1) and (4:1) NiFe2O4 MNPs were in the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…In another research study by Soleimani Lashkenari et al, it was suggested that the toxicity of encapsulated NiFe 2 O 4 nanoparticles with PR is highly dependent on the poisonous properties of PR [ 15 ]. This claim was supported by Al-Qasmi et al who demonstrated that NiFe 2 O 4 nanoparticles are not harmful to organ cells at optimal concentrations [ 121 ]. Therefore, it was hypothesised that a lower concentrations of PR/NiFe 2 O 4 nanocomposite would pose no harm to living cells, based on the research of Nazaktabar et al This research indicated that PR is not harmful to tissues [ 16 ].…”
Section: Properties Of Prmentioning
confidence: 85%
“…In another research study by Soleimani Lashkenari et al, it was suggested that the toxicity of encapsulated NiFe 2 O 4 nanoparticles with PR is highly dependent on the poisonous properties of PR [ 15 ]. This claim was supported by Al-Qasmi et al who demonstrated that NiFe 2 O 4 nanoparticles are not harmful to organ cells at optimal concentrations [ 121 ]. Therefore, it was hypothesised that a lower concentrations of PR/NiFe 2 O 4 nanocomposite would pose no harm to living cells, based on the research of Nazaktabar et al This research indicated that PR is not harmful to tissues [ 16 ].…”
Section: Properties Of Prmentioning
confidence: 85%
“…A mixture of chamomile and star anise has anti-motility effects and can decrease induced diarrhea in mice [38]. Furthermore, the results of a new study indicate that synthesized magnetite Fe 3 O 4 , spinel (2:1) and (4:1) NiFe 2 O 4 using an extract of star anise as a green reducing agent showed high biomedical activities against liver carcinoma cells and non-small lung adenocarcinoma cells [39].…”
Section: Other Activitiesmentioning
confidence: 92%
“…The strong magnetic responsiveness enables efficient separation of MNPs under an external magnetic field [7,8]. Currently, the widely used MNPs mainly include nano zero-valent iron (nZVI) [9,10], magnetite (Fe 3 O 4 ) [11,12], and ferric oxide (γ-Fe 2 O 3 ) nanoparticles [13,14]. The main principle of MNPs detection is that when MNPs are added to the sample, the substance to be measured can be extracted from the sample by attracting and concentrating under certain conditions, and then separated and detected under the action of an external magnetic field [15].…”
Section: Introductionmentioning
confidence: 99%